Patterns of information literacy and their predictors among emergency department nurses: a latent profile analysis based on the person-context interaction theory - Chao Wu; Chunyan He; Jiaran Yan; Juan Du; Shizhe He; Zhaohua Ji; Yifei Wang; Hongjuan Lang (BMC Nursing, 2024)
Abstract Background With the development of information technology, information has been an important resource in clinical medicine, particularly within the emergency department. Given its role in patient rescue, the emergency department demands a high level of information literacy from nurses to effectively collect, analyze, and apply information due to the urgency and complexity of emergency nursing work. Although prior studies have investigated the information literacy of nursing staff, little has been undertaken in examining the patterns of information literacy and their predictors among emergency department nurses. Aim To clarify the subtypes of information literacy among nurses in the emergency department and explore the factors affecting profile membership. Methods A cross-sectional study was conducted among a convenience sample of 2490 nurses in the emergency department from April to June 2023. The clinical nurses completed the online self-report questionnaires including the general demographic questionnaire, information literacy scale, self-efficacy scale and social support scale. Data analyses involved the latent profile analysis, variance analysis, Chi-square tests and multivariate logistic regression. Results Four latent profiles were identified: ‘Low information literacy (Class 1)’, ‘Moderate information knowledge (Class 2)’, ‘High information knowledge and support (Class 3)’ and ‘High information literacy (Class 4)’, accounting for 20.14%, 42.11%, 23.36% and 14.39%, respectively. Each profile displayed unique characteristics representative of different information literacy patterns. Age, years of work, place of residence, hospital grade, title, professional knowledge, using databases, reading medical literature, participating in information literacy training, self-efficacy, and social support significantly predicted information literacy profile membership. Conclusions Information literacy exhibits different classification features among emergency department nurses, and over half of the nurses surveyed were at the lower or middle level. Identifying sociodemographic and internal-external predictors of profile membership can aid in developing targeted interventions tailored to the needs of emergency department nurses. Nursing managers should actively pay attention to nurses with low information literacy and provide support to improve their information literacy level. Relevance to clinical practice Insights from the current study of the latent profile analysis are beneficial to hospital managers in understanding the different types of emergency department nurses’ information literacy. These insights serve as a reference for managers to enhance nurses’ information literacy levels.